The decline of Medieval Hellenism in Asia monor and the process of Islamization from the eleventh through the fifteenth century, by Speros Vryonis, Jr. Center fro Medieval and Renaissance Studies, UCLA, 4 - Rexine, John E. (The Greek Review of Social Research, 1974)
[Δε διατίθεται περίληψη / no abstract available]